2007
DOI: 10.1111/j.1399-3046.2007.00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Donor‐specific antibodies by flow single antigen beads in pediatric living donor kidney transplants: Single center experience

Abstract: Flow PRA and SAB are now routinely performed to identify HLA antibodies in the recipient sera. The presence of DSA is considered a risk factor for graft failure. However, this risk is not clearly defined. We reviewed all the pediatric recipients of living donor kidney transplants since Flow PRA and Flow SAB became routinely done at our institution. All children had negative CDC and Flow XMs. Comparison of clinical outcome was done between those with and without pretransplant DSA. Six children had positive DSA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…The significance of pretransplant HLA-DSA has been examined in two studies. Roberti et al [20] saw an excellent outcome of six children with HLA-DSA before living donor RTx, and Verghese et al [21] found impaired renal allograft survival in ten children with pretransplant HLA-DSA. The significance of posttransplant HLA-DSA has been addressed in only one paediatric study: Emonds et al analysed retrospectively postoperative HLA-DSA in ten children who had lost their deceased donor kidney grafts due to rejection 2-68 months after RTx.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The significance of pretransplant HLA-DSA has been examined in two studies. Roberti et al [20] saw an excellent outcome of six children with HLA-DSA before living donor RTx, and Verghese et al [21] found impaired renal allograft survival in ten children with pretransplant HLA-DSA. The significance of posttransplant HLA-DSA has been addressed in only one paediatric study: Emonds et al analysed retrospectively postoperative HLA-DSA in ten children who had lost their deceased donor kidney grafts due to rejection 2-68 months after RTx.…”
Section: Discussionmentioning
confidence: 98%
“…The significance of HLA-DSA before RTx has been reported in two studies [20,21], and one study has examined the role of posttransplant HLA-DSA on graft survival [22]. The aim of our study was to examine how commonly HLAab are detected in paediatric RTx patients posttransplant by analysing routine serum samples taken at various times after RTx.…”
Section: Introductionmentioning
confidence: 98%
“…While the SAB assays are extremely sensitive and specific for the detection of DSA, they are capable of detecting HLA alloantibodies that are not evident in cell‐based FCXM. While some describe these FCXM‐negative/SAB‐positive alloantibodies as clinically irrelevant (6), others found these antibodies to be associated with impaired graft function (7, 8). To address the uncertainty of the clinical relevance of FCXM‐negative/SAB‐positive alloantibodies, we designed a retrospective study of pediatric renal allograft recipients to assess the prevalence of low levels of DSA that are undetected by cross‐match but positive by SAB in pediatric renal transplant recipients.…”
mentioning
confidence: 99%
“…Some small studies have been performed in children and the results are inconsistent. 5,35,36 which protocol is better? As mentioned before, each protocol has some advantages and some disadvantages.…”
Section: Who Needs Desensitization Treatment?mentioning
confidence: 99%
“…However, controversies remain regarding the association between the results of this test and the outcome of transplant. 5 It is thought that CDC-AHG is sufficient for predicting hyperacute rejection. Patients with low titer anti-HLA antibodies with negative CDC and positive flow cytometry may be involved by acute cellular and/or humeral rejection but not involved by hyperacute rejection.…”
Section: Treatment Update Of Sensitized Pediatric Kidney Transplantmentioning
confidence: 99%